2015
DOI: 10.1371/journal.pone.0143185
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculate Characteristics Depend on Social Environment in the Horse (Equus caballus)

Abstract: Sperm competition theory predicts semen characteristics to be affected by the social environment. We used the polygamous horse (Equus caballus) to experimentally study within-subject plasticity in response to different social environments. Stallions were sequentially exposed, over a period of 8 weeks each, to other stallions and then singly to mares, or vice versa (in adjacent boxes separated by grills). Ejaculates were collected to determine semen characteristics. Highest sperm numbers were found in stallions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…In contrast to the long-term exposure, short-term exposure seems to only affect semen volume and the ability of seminal fluids to support sperm motility and longevity, but it does not seem to affect total sperm counts. This suggests that either long-term exposure to certain social situations enhance sperm production and hence sperm number per ejaculate, or that the present treatment (oestrous versus dioestrous stimulus mare) provokes a different response than the treatments in Burger et al 3940…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In contrast to the long-term exposure, short-term exposure seems to only affect semen volume and the ability of seminal fluids to support sperm motility and longevity, but it does not seem to affect total sperm counts. This suggests that either long-term exposure to certain social situations enhance sperm production and hence sperm number per ejaculate, or that the present treatment (oestrous versus dioestrous stimulus mare) provokes a different response than the treatments in Burger et al 3940…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies on horses that were based on long-term exposure demonstrated that semen characteristics are plastic and that they depend on the social environments the stallions experience. Stallions showed increased sperm number per ejaculate after exposure to other stallions than after exposure to one mare only39, and ejaculates contained more sperm cells after exposure to mares that were predicted to be more attractive than after exposure to mares that were predicted to be less attractive40 (attractiveness being predicted by the sharing of alleles of the major histocompatibility complex4041). Both conditions tested in Burger et al 3940.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to sperm competition have been observed among external fertilizers (Vladic and Jarvi 2001;Flannery et al 2013;Locatello et al 2013) but remain debated for internal fertilizers (Froman et al 2002;Cornwallis and Birkhead 2006;Pizzari and Parker 2009;Lemaître et al 2012;Schradin et al 2012;Burger et al 2015). Higher sperm velocity led to an enhanced fertilization success in competitive environments (Gage et al 2004;Malo et al 2005;Evans et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Types of data transformations are indicated in brackets 2012; Schradin et al 2012;Burger et al 2015). As mentioned in the BIntroduction^section, the method that we used to collect ejaculate provides different values for these traits compared to a natural ejaculation (Mattner and Voglmayr 1962;Moore 1985).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude that longer exposure to the same type of mare would affect sperm velocity. Burger et al [37] compared longer periods of exposure to stallions or to mares (eight weeks each) and found one of three sperm velocity measures (VCL) to be elevated when stallions were exposed to other stallions. However, very short exposures to a novel ovariectomized mare did not seem to influence strategic ejaculation: the MHC of the teaser mare during semen collection did not produce significant effects on any semen characteristics.…”
Section: Discussionmentioning
confidence: 99%